1993
DOI: 10.1073/pnas.90.23.11212
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic sorghum plants via microprojectile bombardment.

Abstract: Transgenic sorghum plants have been obtained after microprojectile bombardment of immature zygotic embryos of a drought-resistant sorghum cultivar, P898012. DNA delivery parameters were optimized based on transient expression of R and Cl maize anthocyanin regulatory elements in scuteflar cells. The protocol for obtaining transgenic plants consists of the delivery of the bar gene to immature zygotic embryos and the imposition of bialaphos selection pressure at various stages during culture, from induction of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
123
0
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(128 citation statements)
references
References 29 publications
1
123
0
4
Order By: Relevance
“…During the first decade of sorghum transformation studies, there are only a few reports of successful recovery and analysis of transgenic sorghum plants (Casas et al, 1993;Casas et al, 1997;Zhu et al, 1998). So far, PDS-1000/He gene delivery device of Biorad laboratories, Richmond, California has been the most common and successful device used for direct gene transfer.…”
Section: Biolistic or Particle Or Microprojectile Bombardment Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…During the first decade of sorghum transformation studies, there are only a few reports of successful recovery and analysis of transgenic sorghum plants (Casas et al, 1993;Casas et al, 1997;Zhu et al, 1998). So far, PDS-1000/He gene delivery device of Biorad laboratories, Richmond, California has been the most common and successful device used for direct gene transfer.…”
Section: Biolistic or Particle Or Microprojectile Bombardment Methodsmentioning
confidence: 99%
“…The disadvantage of the protoplast or cell suspensions is that the method is laborious, needs special skills, tends to be cultivar specific and have very low regeneration frequency. Casas et al (1993) were first to report successful transformation of sorghum immature embryos via biolistic method of gene transfer. They reported that among the surviving calli, only a few exhibited shoot development indicating regeneration of plants at low frequency.…”
Section: Explants For Transformation and Plant Regenerationmentioning
confidence: 99%
See 3 more Smart Citations